MICKIEWICZ’S IMAGOLOGICAL MIRRORS - Kuziak, Michał (Porównania, 2018)
The article discusses Mickiewicz’s imagological discourse. It served to construct projects related to culture and literature and more broadly to the identity relating to the vision of Poland and Slavia. This discourse is changing and heterogeneous. It involves not only a reflection of the romantic thinking about the nation and nationalities but also the testimony of inventing national traditions under oppression, threats of nation deprived of state existence.